2023
DOI: 10.1186/s12891-023-06932-7
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic effect and safety evaluation of oxidized regenerated cellulose in total knee arthroplasty- a randomized controlledtrial

Bowei Li,
Wenjie Pan,
Xiaobo Sun
et al.

Abstract: Background Oxidized regenerated cellulose (ORC) is a type of biodegradable hemostatic material, which has been widely used in the field of surgery. However, its hemostatic effect in patients undergoing total knee arthroplasty (TKA) is uncertain. Accordingly, this study investigated the effectiveness and safety of ORC in patients receiving TKA. Methods Seventy patients undergoing unilateral TKA were randomized into blank control group and ORC (2 pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…In recent years, ORC powder has been used as an absorbable hemostatic agent in different clinical fields, including neurosurgery, thoracic surgery, general surgery, urologic surgery, and gynecologic surgery [ 7 ]. Although there is a report on the hemostatic effect and safety of the fiber form of ORC in TKA surgery, few studies have reported on its powder form [ 8 ]. The powder form of ORC remains a concern for its inability to remove excessive foreign bodies, while its fiber form is notably easy to remove after hemostatic use.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ORC powder has been used as an absorbable hemostatic agent in different clinical fields, including neurosurgery, thoracic surgery, general surgery, urologic surgery, and gynecologic surgery [ 7 ]. Although there is a report on the hemostatic effect and safety of the fiber form of ORC in TKA surgery, few studies have reported on its powder form [ 8 ]. The powder form of ORC remains a concern for its inability to remove excessive foreign bodies, while its fiber form is notably easy to remove after hemostatic use.…”
Section: Introductionmentioning
confidence: 99%